ECOLOGICAL STATUS AND ANALYSIS OF CARBON STOCKS OF TWO SEAGRASS COMMUNITIES IN PANTAI LIPI PULAU PARI, KEPULAUAN SERIBU, DKI JAKARTA - Khoirunnisa, Intan
Global climate change has occurred as a result of an increase in greenhouse gas concentrations, especially CO2 in the atmosphere caused by anthropogenic activities. The blue carbon concept underlines the importance of marine and coastal ecosystems in absorbing and storing carbon, thus playing an important role in climate control. Conservation of blue carbon ecosystems, such as seagrass beds, needs to be conducted as one of the climate change mitigation efforts. This study aims to determine the ecological status and carbon stock of the seagrass ecosystem in Pantai LIPI Pulau Pari, Kepulauan Seribu, DKI Jakarta. In this study, two different seagrass beds were compared. Based on a preliminary field survey, it was found that seagrass in the first location tended to be monospecific, while seagrass in the second location was a multispecific community. Field data were obtained using the line intercept transect (LIT) method which stretched 50 m perpendicular to the coastline using 15 plots measuring 1x1 m. These plots were used to describe the structure of the seagrass community including density, frequency, cover, and importance value index, and determine carbon stock of seagrass biomass (aboveground and belowground) and seagrass substrate. Estimation of carbon stock followed the methodology of Howard et al. (2014) and Rustam et al. (2019). Results of the study found that there were differences between the two locations; the monospecific community found in turbid water and muddy substrates is dominated by Enhalus acoroides species, while the multispecific community found in clear water with muddy sand substrate and coral fragments consists of Enhalus acoroides, Thalassia hemprichii, and Halodule uninervis. The ecological status of both communities were determined based on percent cover, in accordance to the Decree of the Minister of Population and Environment number 200 of 2004. Both communities are in the healthy category with the multispecific community having slightly higher cover percentage than the monospecific community, although statistical analysis showed no significant difference between two communities. Seagrass biomass carbon stocks (aboveground and belowground) in the monospecific community was higher compared to the multispecific community, partly affected by species composition and high belowground carbon stocks. Seagrass substrate carbon stocks in the monospecific community was higher than in the multispecific community, which can be associated with the type of substrate, species composition, and hydrodynamics of water. The results from this research showed that substrate carbon stocks have a major contribution to blue carbon.